Digital Encyclopedia of Applied Physics 2009
DOI: 10.1002/3527600434.eap673
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels

Abstract: Ion channels catalyze the transmembrane movement of small inorganic ions across biological membranes. They do so by forming continuous, hydrophilic pores through which ions can cross the barrier imposed by the lipid bilayer hydrophobic core. Ion channels serve many functions: they underlie the changes in membrane potential that control many cell functions, including the propagated electrical signaling (the action potentials) in electrically excitable cells; they allow for the bulk movement of ions across cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 172 publications
0
3
0
Order By: Relevance
“…Adjustments of conductance in response to chemical stimuli are an essential biological function of canonical ion channels in living cells [18,21,22], and such features may be replicated in vitro for sensing purposes. However, ion channel reconstitution in artificial membrane systems is not always an easy task [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Adjustments of conductance in response to chemical stimuli are an essential biological function of canonical ion channels in living cells [18,21,22], and such features may be replicated in vitro for sensing purposes. However, ion channel reconstitution in artificial membrane systems is not always an easy task [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some natural systems have evolved in directing the Brownian motion by using ion/molecular channels. 9,10 Enzymes, however, often utilize aromatic groups in their backbone as gates for controlling the rate by which molecules access their active site and thereby the selectivity of chemical reactions occurring in their interior. 11 Notably, the function of ion/molecular channels as well as enzymes relies on molecular recognition allowing fine-tuning of the rate by which molecules travel and change their environment (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that lysenin channels alter their conformation by the movement of a gate coupled to a charged voltage domain sensor when under the influence of an external electric field [ 6 ], which is functionally similar to many voltage-gated ion channels [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Structural data reveals the presence of hinge-like, flexible structures essential for pore formation [ 19 , 20 , 21 ] which may allow the elusive voltage domain sensor to move.…”
Section: Introductionmentioning
confidence: 99%